Expansion or Depletion of T Follicular Helper Cells During HIV Infection: Consequences for B cell Responses - O. Onabajo, Olusegun; J. Mattapallil, Joseph (Current HIV Research, 2013)
HIV infection is characterized by aberrant B cell responses and B cell dysfunction. These dysfunctional responses have been extensively documented in peripheral blood and organized lymphoid tissues such as the lymph nodes. Though the loss of CD4 T cell help has been thought to play a key role in dysfunctional B cell responses, recent studies have implicated a subset of CD4 T helper cells called the T follicular helper (Tfh) cells in this process. Tfh cells interact with B cells and play a key role in mediating the germinal center reaction, and driving the differentiation and maturation of B cells. Why Tfh expands in some HIV infected individuals as compared to their loss in others is still not clear. Here we review some of the recent developments in the field and discuss the implications of Tfh cell dysregulation on B cell responses during HIV infection.
Keywords: Tfh